Perinatal deaths from birth defects in Hunan Province, China, 2010-2020 - Xu Zhou; Donghua Xie; Jian He; Yurong Jiang; Junqun Fang; Hua Wang (BMC, 2023)
Abstract Objective To describe the perinatal mortality rate (PMR) of birth defects and to define the relationship between birth defects (including a broad range of specific defects) and a broad range of factors. Methods Data were obtained from the Birth Defects Surveillance System in Hunan Province, China, 2010-2020. The prevalence rate (PR) of birth defects is the number of birth defects per 1000 fetuses (births and deaths at 28 weeks of gestation and beyond). PMR is the number of perinatal deaths per 100 fetuses. PR and PMR with 95% confidence intervals (CI) were calculated using the log-binomial method. Chi-square trend tests (χ 2 trend ) were used to determine trends in PR and PMR by year, maternal age, income, education level, parity, and gestational age of termination. Crude odds ratios (ORs) were calculated to examine the association of each maternal characteristic with perinatal deaths attributable to birth defects. Results Our study included 1,619,376 fetuses, a total of 30,596 birth defects, and 18,212 perinatal deaths (including 16,561 stillbirths and 1651 early neonatal deaths) were identified. The PR of birth defects was 18.89‰ (95%CI: 18.68-19.11), and the total PMR was 1.12%(95%CI: 1.11-1.14). Birth defects accounted for 42.0% (7657 cases) of perinatal deaths, and the PMR of birth defects was 25.03%. From 2010 to 2020, the PMR of birth defects decreased from 37.03% to 2010 to 21.00% in 2020, showing a downward trend (χ 2 trend  = 373.65, P < 0.01). Congenital heart defects caused the most perinatal deaths (2264 cases); the PMR was 23.15%. PMR is highest for encephalocele (86.79%). Birth defects accounted for 45.01% (7454 cases) of stillbirths, and 96.16% (7168 cases) were selective termination of pregnancy. Perinatal deaths attributable to birth defects were more common in rural than urban areas (31.65% vs. 18.60%, OR = 2.03, 95% CI: 1.92-2.14) and in females than males (27.92% vs. 22.68%, OR = 1.32, 95% CI: 1.25-1.39). PMR of birth defects showed downward trends with rising maternal age (χ 2 trend  = 200.86, P < 0.01), income (χ 2 trend  = 54.39, P < 0.01), maternal education level (χ 2 trend  = 405.66, P < 0.01), parity (χ 2 trend  = 85.11, P < 0.01) and gestational age of termination (χ 2 trend  = 15297.28, P < 0.01). Conclusion In summary, birth defects are an important cause of perinatal deaths. Rural areas, female fetuses, mothers with low maternal age, low income, low education level, low parity, and low gestational age of termination were risk factors for perinatal deaths attributable to birth defects. Future studies should examine the mechanisms. Our study is helpful for intervention programs to reduce the PMR of birth defects.